2018
DOI: 10.1177/1368430218761587
|View full text |Cite
|
Sign up to set email alerts
|

Combatting gender discrimination: A lack of fit framework

Abstract: The past 50 years have been marked by considerable progress for women in the workplace, reflected in increased labor force participation rates and a shrinking wage gap (U.S. Bureau of Labor Statistics, 2017). Yet, these advances can sometimes be deceptive in their implications. Although a holistic view of organizations might suggest that gender parity has been achieved, a segmented breakdown of professions, positions, and industries offers a far less favorable picture. Today, women remain underrepresented in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(130 citation statements)
references
References 97 publications
5
109
0
3
Order By: Relevance
“…Given the hypothesized role of gender stereotypes and hierarchy in all three forms of sex discrimination, does increasing WGD—by attenuating both—help to mitigate sex discrimination? Turning first to direct discrimination, as Heilman and Caleo () note, one intervention that can be expected to attenuate gender stereotypes, and the mismatch between feminine stereotypes and traditionally masculine roles, is having greater numbers of women in those roles. Similarly, role congruity theory suggests that, as women become better represented in masculine occupational roles, stereotyping of women as communal will decrease (Koenig & Eagly, ).…”
Section: Justice and Workplace Gender Diversitymentioning
confidence: 99%
“…Given the hypothesized role of gender stereotypes and hierarchy in all three forms of sex discrimination, does increasing WGD—by attenuating both—help to mitigate sex discrimination? Turning first to direct discrimination, as Heilman and Caleo () note, one intervention that can be expected to attenuate gender stereotypes, and the mismatch between feminine stereotypes and traditionally masculine roles, is having greater numbers of women in those roles. Similarly, role congruity theory suggests that, as women become better represented in masculine occupational roles, stereotyping of women as communal will decrease (Koenig & Eagly, ).…”
Section: Justice and Workplace Gender Diversitymentioning
confidence: 99%
“…Such beliefs can be general, or may be concerned with specific roles such as those involving leadership or technical skills, or specific social groups such as women or ethnic minorities. The prejudiced belief system described above is based, in part, on stereotypes about these stigmatized groups' purported inherent attributes, and how poorly these attributes are thought to match the behaviors required in specific roles or the workplace in general (Eagly & Karau, 2002;Heilman & Caleo, 2018).…”
Section: Attitudes Towards Workplace Diversitymentioning
confidence: 99%
“…Again, central to this theory is a consideration of gender stereotypes -in particular, preconceptions in view of what men and women ought to be. 60 In addition, a study conducted by Forsyth, Heiney, Wright (1997) researched role-incongruence in small groups led by women who applied relationship-or task-oriented leadership styles. It was revealed that conservative group participants reacted more negatively to female taskoriented leaders and rated the female leader lower regarding collegiality.…”
Section: Gender and Stereotypesmentioning
confidence: 99%